A new subgenus and species of Topomyia (Diptera: Culicidae: Sabethini) based on a remarkable male mosquito from Sabah, Malaysia - Harbach, Ralph E.; Culverwell, C. Lorna (Zootaxa, 2014)
Miyagiella Harbach, subgen. nov., is introduced as a new subgenus of Topomyia Leicester for a remarkable male mosquito, Topomyia discors Harbach, sp. nov., from Sabah, Malaysia. A diagnosis of the subgenus is provided that features unique anatomical characters of the genitalia of the holotype male. Miyagiella is very distinct from the two previously recognised subgenera of Topomyia, but is perhaps more closely related to the nominotypical subgenus than to subgenus Suaymyia Thurman. Salient differences that distinguish the three subgenera are contrasted; the holotype male of To. discors is described and its unique genitalia are illustrated.